PENGUATAN MANAJEMEN RISIKO DI ORGANISASI KOMUNITAS MELALUI IDENTIFIKASI, MITIGASI, DAN PEMULIHAN BENCANA - Ahmad Jet Alamin A; Margono; Heni A. Adilan (Jurnal Industri Kreatif dan Inovatif, 2025)
This community service program (PkM) aims to strengthen risk management within community organizations to improve their readiness for disasters/incidents through three main pillars: risk identification, mitigation and preparedness, and recovery. Common issues include hazard and vulnerability mapping that have not yet been documented, unclear emergency response standard operating procedures (SOPs), uninventoried equipment/logistics, unstructured crisis communication, and limited post-incident learning. The intervention is implemented through risk assessment workshops at the local area level, developing a risk register and risk prioritization, training on SOPs and conducting simulations, establishing a simple incident command structure, formulating a recovery plan (including basic psychosocial support), and creating a preparedness dashboard. The main outputs include community risk management plan documents, risk maps, emergency response SOPs, crisis communication plans, logistics lists, and a 30–90 day recovery plan. The primary targets are community leaders, volunteers, and local partners. Evaluation is conducted using KPIs to measure improvements in volunteer preparedness and the effectiveness of the developed SOPs.